I can make you confident : the power to go for anything you want! - McKenna, Paul, 1963- (Sterling, 2010)
Dr. McKenna demonstrates the latest techniques to stop fear and desperation and create massive amounts of confidence and self-belief instantly, whether it's mastering the fear of public speaking or feeling more self-assured in social, business, and romantic situations.